CHINGIZ AITMATOV METAPHOR OF THE NOVEL "AND THE DAY LASTS LONGER THAN A CENTURY" 93% - Эсанова Феруза Насриддиновна (Web of Journals Publishing, 2024)
The purpose of the article is to study the phenomenon of metaphor in the novel by Ch. Aitmatov "And the Day Lasts Longer Than a Century". Attention is paid primarily to the symbolism of the novel. It is contained both in its text and in the title itself. Metaphors have become necessary not only because of the intrusion of scientific and technological advances into the realm of fiction, but because the world in which man lives is contradictory and disharmonious.
Keywords: metaphor, image, metaphoric model, man, metaphorical technique, harmony, nature, anthropomorphic metaphors.